Tea Trade in Russian Empire in Middle of 19th Century - K. A. Abdrakhmanov (Научный диалог)
The business activity of merchants of the middle of the 19th century, who chose the tea trade as the main area of their investments, is investigated. The analysis of the Russian tea trade in the middle of the 19th century in the context of its organizational specifics is very limitedly presented in Russian historiography, which confirms the novelty of this scientific study. The key moments of the organization of trade operations with the Chinese in Kyakhta are considered. The range of problems typical for the entrepreneurial practice of tea merchants of this era is presented and analyzed. Emphasis is placed on the trade in smuggled tea and the production of its surrogate versions as the main obstacles to the productive work of the tea market in the interests of the merchants and the state. It is noted that the trade in illegal goods was carried out by colleagues who did not know how or did not want to make a profit in an honest way, and the marginal phenomenon itself was so massive that the merchants could not liquidate the illegal market on their own. As a result, in order to resolve many issues, merchants had to interact with various structures of the country’s authorities. It is shown that the remote format of interaction between large entrepreneurs and their sales agents in Kyakhta had certain inconveniences and brought profits to tea business owners much less than the possible maximum.